The customer-funded business : start, finance, or grow your company with your customers' cash - Mullins, John W. (John Walker) (Wiley, 2014)
Who needs investors? More than two generations ago, the venture capital community - VCs, business angels, incubators and others - convinced the entrepreneurial world that writing business plans and raising venture capital constituted the twin centerpieces of entrepreneurial endeavor. They did so for good reasons: the sometimes astonishing returns they've delivered to their investors and the astonishingly large companies that their ecosystem has created. But the vast majority of fast-growing companies never take any venture capital. So where does the money come from to start and grow their comp.